The colony forming efficiency assay for toxicity testing of nanomaterials—Modifications for higher-throughput - Rundén-Pran, Elise; Mariussen, Espen; El Yamani, Naouale; Elje, Elisabeth; Longhin, Eleonora Marta; Dusinska, Maria (Frontiers in Toxicology, 2022)
To cope with the high number of nanomaterials (NMs) manufactured, it is essential to develop high-throughput methods for in vitro toxicity screening. At the same time, the issue with interference of the NM with the read-out or the reagent of the assay needs to be addressed to avoid biased results. Thus, validated label-free methods are urgently needed for hazard identification of NMs to avoid unintended adverse effects on human health. The colony forming efficiency (CFE) assay is a label- and interference free method for quantification of cytotoxicity by cell survival and colony formation. The CFE assay has shown to be compatible with toxicity testing of NMs. Here we present an optimized protocol for a higher throughput set up.